2020
DOI: 10.1096/fj.202000063r
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of human intestinal organoids in vitro facilitates colonization by commensal lactobacilli by reinforcing the mucus layer

Abstract: Lactobacilli, which are probiotic commensal bacteria that mainly reside in the human small intestine, have attracted attention for their ability to exert health-promoting effects and beneficially modulate host immunity. However, host epithelial-commensal bacterial interactions are still largely unexplored because of limited access to human small intestinal tissues. Recently, we described an in vitro maturation technique for generating adult-like, mature human intestinal organoids (hIOs) from human pluripotent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 61 publications
1
24
0
Order By: Relevance
“…It has been reported that butyrate could upregulate the expression of MUC2 and MUC5A, increase the epithelial barrier function, induce the assembly of tight junctions and enhance the glycosylation of mucus in Caco-2 and HT-29 cells (Gaudier et al, 2004;Peng et al, 2009;Nielsen et al, 2018). Probiotics-derived short-chain fatty acids(SCFAs) could regulate epithelial barrier, promote mucus release, and induce differentiation of intestinal epithelial cells (Son et al, 2020). The bioactive components secreted by probiotic bacteria could also contribute to the expression of mucins and changes in O-glycosylation of mucins (Da Silva et al, 2014;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that butyrate could upregulate the expression of MUC2 and MUC5A, increase the epithelial barrier function, induce the assembly of tight junctions and enhance the glycosylation of mucus in Caco-2 and HT-29 cells (Gaudier et al, 2004;Peng et al, 2009;Nielsen et al, 2018). Probiotics-derived short-chain fatty acids(SCFAs) could regulate epithelial barrier, promote mucus release, and induce differentiation of intestinal epithelial cells (Son et al, 2020). The bioactive components secreted by probiotic bacteria could also contribute to the expression of mucins and changes in O-glycosylation of mucins (Da Silva et al, 2014;Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mucus is also the first barrier protecting the gut from being invaded by the bacteria. Mucus is critical for the intestinal health since disruption of this boundary will probably result in bacterial penetration of mucus barrier and induce intestinal inflammation (Liu et al, 2020;Sharma et al, 2020;Son et al, 2020). It has been reported that gut bacteria could colonize the intestinal mucus layer in vivo and adhere to HT-29 cell in vitro (Altamimi et al, 2016;Engevik et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to co-culture with human cells, crosstalk with the microbial community in an in vitro model is much more challenging. Several models, including Transwell inserts [ 109 ], intestinal organoids [ 110 ], and specialized bioreactor models [ 111 ], were tested to sustain complex populations of human intestinal microbiota in contact with living human tissues to mimic physiologically and pathologically related human intestine-microbiome crosstalk. In Transwell models, co-culture with bacteria could only be carried out within hours, due to the uncontrolled overgrowth of bacteria [ 112 ].…”
Section: Current Intestine Modelsmentioning
confidence: 99%
“…It has also been demonstrated that lactobacilli are capable of exerting a modulating effect on the host's immune system. However, epithelial-commensal bacterial interactions with the host organism have been hardly studied due to limited access to the tissues of the human small intestine (Son et al 2020). Some lactobacilli species have developed the ability to stimulate the generation of reactive oxygen species (ROS) in epithelial cells, which leads to the proliferation of intestinal epithelial cells through processes requiring the catalytic action of Nox1.…”
Section: Using Organoids To Model Infectious Diseases and Study Adaptmentioning
confidence: 99%